Analisis Kemampuan Pemecahan Masalah Matematika Siswa Kelas VII Pada Materi Segitiga dan Segiempat - Hartati, Leny; Adawiyah, Robiatul (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
Problem-solving skills are basic mathematical skills that must be mastered after students learn mathematics. This study aims to describe the mathematical problem solving ability of grade VII MTs Riyadlotul 'Uqul Tangerang students. The research method used is descriptive qualitative research with the sampling technique used is the purposive sampling method. The subjects in this study were 31 students of grade VII MTs Riyadlotul 'Uqul Tangerang, where three students were selected based on their ability to solve math problems at a high, medium, or low level. Data collection techniques in this study are by tests, interviews, and documentation. The results showed that the mathematical problem solving ability of grade VII students of Mts Riyadlotul 'Uqul on triangular and quadrilateral material was still relatively low according to the Polya indicator. The ability to solve high, medium and low categories of mathematical problems, obtained the highest achievement of students on the four indicators of solving mathematical problems is on the indicator of understanding problems. Students are already able to identify what is known and asked appropriately. Meanwhile, the lowest achievement of students is in the indicator of re-examining or interpreting the results obtained.